الدرس النحوي والصرفي عند الغربيين واللغويين العرب في ضوء التراث اللغوي: دراسة وصفية تحليلية - Nur Syuhada binti Roslan (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This study aims at investigating the attitude of contemporary Arab and Western linguists towards classical Arabic studies and the way they interact with these in terms of acceptance or declination, and the invitation to re-read modern linguistics and its integration with classical Arabic studies. This study discusses Western studies on syntax and morphology and explains the attitude of contemporary Arab linguists. It also explores the attitude of Western linguists towards classical Arabic studies and their acceptance, and their contributions to modern linguistics studies. This study was conducted using descriptive analysis. It has reached significant results, in which, the development of modern syntax and morphological studies by contemporary Western linguists has affected modern Arabic studies, and there are Arab linguists who have adopted this study in the field of Arabic syntax and morphology, among them Tammam Hassan, Ibrahim Anis and Abdel Kader Fassi Fehri, and there are scholars who rejected linguistics studies by the West, among them Ali Harb. This research has confirmed that some of the Western linguists admit that classical Arabic studies have made significant contributions to modern linguistics, among them Johann Wilhelm Fück, Michael G. Carter, Kees Versteegh and Gotthelf Bergsträsser. Lastly, this study indicates that the contributions of classical Arabic scholars are no less valuable than the contributions of contemporary scholars in the study of Arabic syntax.